Mechanical and biological approaches to alleviate soil compaction in tropical soils: assessed by root growth and activity (Rb uptake) of soybean and maize grown in rotation with cover crops - Rosolem, C. A. [UNESP]; Pivetta, L. A. (Wiley-Blackwell, 2017)
Chiselling has been used to alleviate soil compaction but cover crops with deep, vigorous roots can improve root growth and activity of the cash crop for a longer time. The determination of root activity in addition to root mass or length may improve the understanding of plant response to compaction. The objective of this experiment was to evaluate root growth and activity as affected by the alleviation of soil compaction using mechanical and biological methods. The experiment was conducted in Botucatu, SAo Paulo, Brazil, from 2009 to 2011, on a clay, Typic Rhodudalf soil. Crop rotations including pear millet (Pennisetum glaucum), soybean (Glycine max), grain sorghum (Sorghum bicolor), maize (Zea mays), ruzi grass (Brachiaria ruziziensis) and castor bean (Ricinus communis) in plots, either chiselled or not. Root growth was assessed by core sampling and root activity was determined indirectly using rubidium injected at several depths as a marker. Root activity was instrumental in interpreting the effects of tillage and crop rotations on soil amelioration. Compared with the initial compacted condition, chiselling increased root growth and activity just for the first 18months of the experiment, but crop rotations, mainly including ruzi grass and castor bean, increased root growth and activity in the soil profile from the second year on. Generally, root mass was poorly correlated with root activity, except in the case of ruzi grass. Introduction of ruzi grass plus castor bean into the cropping system improves not only root growth and activity in the soil profile but also soybean yield.
Keywords: Cropping systems; root evaluation; tillage; rubidium